Cognitive Load Theory in Computing Education Research: A Review - Duran, Rodrigo; Zavgorodniaia, Albina; Sorva, Juha (ACM Transactions on Computing Education, 2022)
One of the most commonly cited theories in computing education research is cognitive load theory (CLT), which explains how learning is affected by the bottleneck of human working memory and how teaching may work around that limitation. The theory has evolved over a number of decades, addressing shortcomings in earlier versions; other issues remain and are being debated by the CLT community. We conduct a systematic mapping review of how CLT has been used across a number of leading computing education research (CER) forums since 2010. We find that the most common reason to cite CLT is to mention it briefly as a design influence; authors predominantly cite old versions of the theory; hypotheses phrased in terms of cognitive load components are rare; and only a small selection of cognitive load measures have been applied, sparsely. Overall, the theory's evolution and recent themes in CLT appear to have had limited impact on CER so far. We recommend that studies in CER explain which version of the theory they use and why; clearly distinguish between load components (e.g., intrinsic and extraneous load); phrase hypotheses in terms of load components "a priori;" look further into validating different measures of cognitive load; accompany cognitive load measures with complementary constructs, such as motivation; and explore themes such as collaborative CLT and individual differences in working-memory capacity.